(untitled) (International journal of artificial intelligence, 2024)
The article describes how proverbs with a gender component have their own semantic characteristics from the perspective of nationality comparing them in English, Russian and Uzbek languages. In particular, the study of the gender characteristics of proverbs in English, Russian and Uzbek is planned to be studied through six types of semantic groups: marriage, love, appearance, fatherhood/motherhood, character (behavior) and old age, and is analyzed through three folk proverbs.